Health system, Colombian armed conflict and humanitarian international right - Laverde de Botero, Laura Alicia; López Jaramillo, Jorge Iván; Ochoa Idárraga, Alba Lucía (Investigación y Educación en Enfermería, 2008)
This paper deals with the preparation of university students, in the health area, regarding the protection of humanitary and health missions in zones of armed conflict. ";Medellin 2000"; was a descriptive and exploratory research devoted to identify the perceptions students have about the armed conflict in Colombia. Participants were asked to answer questions about their perceptions of the actors involved in the conflict, the geographical region involved, the effects of conflict in the health area, the fears they had about the conflict, and their knowledge about International Humanitary Law. The results suggest some strategies for the education of health students and health workers in the area of international humanitary law. The integral conflict in Colombia was recognized by 92% of the students nearing graduation. Fifty per cent had information about protection providen by International Humanitary Law. Ninety eight per cent received that information through tv. For thirty eight per cent of them that information was part of the curriculum. Ninety eight per cent perceives risk of life as the principal effect of the conflict in the health sector while 91% do not know who to react facing the risk situations generated by the conflict. Seventy five per cent is afraid to travel and 89% has not received university training about professional exercise in conflict zones. The findings may motivate universities and health institutions to train their personnel in conflict resolution and rights, obligations and protection of the medical mission in internal armed conflicts. Key words: armad conflict, medical mission, International Humanitarian Law, Colombia